Eudemonic intellectual property: patents and related rights as engines of happiness, peace, and sustainability - Derclaye, Estelle (Vanderbilt University Law School, 2012)
The predominant justification for most intellectual property rights is the incentive theory or utilitarian rationale. Behind this justification lies the Western idea of progress and its derivatives: liberalism, capitalism, and consumerism. After having shown that the predominant justification for intellectual property rights is the incentive theory, which rests on the idea of progress, this Article traces back the history of the idea and shows its parochialism in both time and space. The Article next shows that the progress ideology rests on assumptions that are either wrong or impossible to prove and therefore propounds that it must be abandoned, or if not, at least deeply rethought or reformed. This Article proposes the values of happiness, peace, necessity, and sustainability as an alternative basis for patents and related rights. These universal values give a legitimate and solid foundation to patents and related rights. The Article suggests ways to integrate the new justification in the substantive law, and counters the arguments against the new justification. In order to answer the question this Article addresses, it is necessary to take both a historical and philosophical perspective. As intellectual property rights are Western in origin, this Article takes a Western perspective by reviewing the two most representative Western legal systems, the European Union and the United States. The philosophical and economic history of the West is compared with that of the Muslim world and some Asian countries, namely China and Japan, because they also represent a very large part of the world.